Effects of environmental ergonomic factors towards muscles activities for lifting task - Che Mohammad Nizam, Che Kamaruddin (2019)
The rubber industry is one of the dominant industries, contributing to the growth of the Malaysian economy. Currently, most of the production processes in the rubber industry are either manually operated or semi-automatic. This study investigates the effect of ergonomic environmental factors, which are including lighting and temperature with human muscle activity. It was tested while workers performing the lifting activity for loading and unloading with a constant load of 25kg. The correlation between muscle activities with different illuminance and temperature level had been analysed. For the first phase, fieldwork measurement had been conducted at one selected rubber industries located in Temerloh, Pahang. Temperature and illuminance level were recorded to obtain the actual data while workers performing the task. Lux meter and Wet Bulb Globe Temperature was used and equipment standard operating procedure had been followed. Nine sampling points had been identified based on actual working zone. Interval for both temperature and illuminance readings is ten minutes. This actual measurement and observations data is used in phase two. Subsequently, a laboratory experiment was conducted in the Ergonomic Simulation Chamber located in Universiti Malaysia Pahang for phase two of this research. Six respondents were randomly selected to participate in the experiment. All the respondents were asked to simulate the same work activities which had been done in the production section of the rubber industry. Next, Surface Electromyography (sEMG) was used to measure muscle activities while doing lifting work. An electronic signal was placed at respondents left and right upper body including the right trapezius, right biceps brachii, left trapezius, and left biceps brachii. Three different ergonomic environments i.e. temperature at 20°C, 24°C and 32°C and lighting at 200, l500 and 1000lux had been set up. All the collected data were analysed by using Microsoft Excel. In this experimental study, each respondent carried out the task (loading and unloading a 25kg load) with nine different levels of temperature and illuminance. The result shows that with repeated manoeuvres using load 25 kg at 19oC and 32oC, the tendency of the body muscles for right and left to be fatigue is fast compared to the temperature of 24oC with the level at 200lux, 500lux and 1000lux. There was a significant correlation between human right and left upper body fatigue levels with the temperature of 19oC and 32oC, and lighting 500lux. This can be due to the prolonged exposure of repetitive work while performing loading and unloading activities. The optimum temperature and illumination level for repetitive lifting work were at 24oC and 500lux. This study provides confirmatory evidence; temperature 24°C is suitable for workers to perform their task while the illuminance level does not affect much.